2015
DOI: 10.3855/jidc.5634
|View full text |Cite
|
Sign up to set email alerts
|

Clonal relatedness and resistance patterns of Salmonella Corvallis from poultry carcasses in a Brazilian slaughterhouse

Abstract: Introduction: Salmonella is a major cause of foodborne disease, and poultry products are important contributors to the transmission of this zoonotic pathogen. Although considered to be rare in most countries, Salmonella Corvallis has been reported in specific geographic areas isolated from both human and non-human sources. The aim of this study was to report the occurrence, the antimicrobial resistance profiles including the extended-spectrum beta-lactamase (ESBL) production, and the clonal relatedness of S. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Moreover, the chickens slaughtered at this abattoir were from different farms. Seven S. Corvallis isolates were isolated in the first visit, in which the serotype was also reported in chicken from Brazil with an isolation rate of 7.9% (29). In the present study, the prevalence of S. Kentucky and S. Enteritidis in the slaughterhouse was 44.7 and 32.5%, which was consistent with findings reported in Guangdong province (27,28).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the chickens slaughtered at this abattoir were from different farms. Seven S. Corvallis isolates were isolated in the first visit, in which the serotype was also reported in chicken from Brazil with an isolation rate of 7.9% (29). In the present study, the prevalence of S. Kentucky and S. Enteritidis in the slaughterhouse was 44.7 and 32.5%, which was consistent with findings reported in Guangdong province (27,28).…”
Section: Discussionsupporting
confidence: 90%
“…Our study found two isolates of Typhimurium in the tap water outside the layer farmhouse, which may be due to Salmonella contamination from animal feces. S. enterica Corvallis is most commonly found in poultry carcasses following the slaughtering process in several countries, including Thailand [13], Brazil [14], Malaysia [15], and China [16]. In this study, the prevalence of Corvallis in laying farm environmental samples was high when compared with the results of Moraes et al [17] and Camba et al [18].…”
Section: Discussionmentioning
confidence: 47%
“…Interestingly, Agona, Corvallis, and Kentucky were reported less frequently in previous studies ( Arnedo-Pena et al, 2016 ), whereas they were the dominant isolates in the current investigation. Additionally, serovar Agona is one of the top 10 serotypes responsible for nosocomial infections in China ( Zhang et al, 2014 ); serovar Corvallis has been reported in Brazil, Germany, and Turkey ( Kocabiyik et al, 2006 ; Fischer et al, 2013 ; Yamatogi et al, 2015 ); and serovar Kentucky was the most common serovar in the United States ( van Duijkeren et al, 2002 ; Galanis et al, 2006 ). The results suggest that Agona, Corvallis, and Kentucky may cause public health concerns in Guangdong.…”
Section: Discussionmentioning
confidence: 99%